Pengolahan Limbah Warna DYA Industri Pencelupan Tekstil dengan Teknologi UV / H2O2/ TiO2 - Hudaya, Tedi; Tunardi, Stephen Reinaldo; Octaviany, Octaviany (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Textile wastewater often contains non-biodegradable as well as toxic dyes, for example Dianix Yellow Ace (DYA). One possible destructive method of treating such waste treatment is the Advance Oxidation Processes (AOPs), in which the oxidation of organic compounds by potent hydroxyl radicals (● OH) occurs. This research had a novelty of combining UV / H2O2 with UV / TiO2 to study the effect of treatment process’ variables, i.e. [H2O2], [TiO2] and initial pH on the rate of degradation as well as the ratio of BOD / COD until biodegradability threshold was reached.  This research employed a Central Composite Design (CCD) experimental design technique that used factorial design and included center points as well as axial points for better accuracy and understanding of the process. CCD helped create a response surface model for optimization and prediction. The variations were the concentration of H2O2 between 0.01 - 1.00 %w, TiO2 concentrations ranging from 0.80 to 3.00 g.L-1 and initial pH between 1 - 11.  The order and reaction rate constants were also determined by measuring the DYA concentrations using a spectrophotometer.  The optimum condition for DYA degradation was found at pH 3, 0.2% H2O2 and [TiO2] 3 g.L-1 with a pseudo first-order rate constant of 0.0524 min-1.  UV irradiation around 75 minutes resulted in DYA removal of 99%.  The wastewater fell into the biodegradable limit after 60 minutes treatment, with a value of BOD / COD ratio was 0.1029 so that the wastewater became biodegradable to be further treated by much cheaper biological method.